The Flesh King - Kadrey, Richard (Kadrey, Richard. Discreet eliminators series, 2025)
Ford, Neuland and Tilda return home after the events of The Pale House Devil to try and make peace with the NYC crime syndicates. But they'll only be welcomed back if they take on a job for free - hunting down, and killing, the Flesh King, a gruesome killer who is stalking the city, leaving a macabre and bloody trail wherever he goes. Caught up in a twisted set of conspiracies and bloodletting, the monster hunters step up to do what they do best once more - take down the unstoppable evil.